2019
DOI: 10.2136/sssaj2018.09.0359
|View full text |Cite
|
Sign up to set email alerts
|

Soil Carbon Accumulation and Nutrient Availability in Managed and Unmanaged Ecosystems of East Tennessee

Abstract: Native woodlot and grassland systems have been converted to a managed turfgrass system with urbanization. Turfgrass systems increased carbon sequestration and nitrogen availability compared with row crop systems. Cool‐season (C3) turfgrasses improved soil physical and chemical properties more than warm‐season (C4) grasses. In the last two decades, urban and suburban lands grew by 34% in the United States, with 16 to 20 million ha maintained under turfgrass systems. Side‐by‐side comparison of turfgrass systems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(63 reference statements)
0
4
0
2
Order By: Relevance
“…Camenzind et al (2016) observed 4.1% increase in water stable aggregates with P application rate of 10 kg ha −1 yr −1 than control in tropical ecosystem. Soil aggregation tends to increase SOC by influencing soil fertility and crop productivity by reducing erosion and controlling air permeability, water infiltration, and nutrient cycling (Singh et al, 2019b;Zhang et al, 2012). Soil aggregates are important agents of SOC retention (Haile, Nair, & Nair, 2008) by occluding C against microbial decomposition (Six, Elliott, & Paustian, 1999;Sollins, Homann, & Caldwell, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Camenzind et al (2016) observed 4.1% increase in water stable aggregates with P application rate of 10 kg ha −1 yr −1 than control in tropical ecosystem. Soil aggregation tends to increase SOC by influencing soil fertility and crop productivity by reducing erosion and controlling air permeability, water infiltration, and nutrient cycling (Singh et al, 2019b;Zhang et al, 2012). Soil aggregates are important agents of SOC retention (Haile, Nair, & Nair, 2008) by occluding C against microbial decomposition (Six, Elliott, & Paustian, 1999;Sollins, Homann, & Caldwell, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Also, a sprinkler infiltrometer was used for WAS instead of commonly used wet sieving. Previous studies reported treatment differences in SOC and WAS from these tested cropping systems when dry combustion and wet sieving, respectively, were used (Nouri, Lee, Yin, Saxton, et al, 2019;Nouri, Lee, Yin, Tyler, et al, 2019;Singh et al, 2019;Singh, Nouri, et al, 2020). 2.…”
Section: Comprehensive Assessment Of Soil Healthmentioning
confidence: 96%
“…C3 grassen veldbeemdgras en rietzwenkgras kunnen meer koolstof opslaan dan C4 gras bermudagras (Singh et al, 2019;Fransluebbers et al, 2002). Rietzwenkgras slaat weer meer koolstof op dan veldbeemdgras .…”
Section: Kruiden In Mengselunclassified